FAIRCLOUGH’S CDA IN THE ACRONYM OF REGONAL NAMES IN BANYUMAS REGENCY - Gigih Ariastuti Purwandari; Rosdiana Puspita Sari (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This research aims to describe the meaning of acronyms of Regional names in Banyumas regency and the background of its making. This research uses Fairclough Critical Discourse Analysis approach. The collecting data technique is taken by interviewing Alan Asprilla (as the acronym video maker) directly and continued by making transcription of the video. The results of the research show that there are three levels of analysis. First, micro analysis shows pronoun “aku” and “kamu” and several dictions. Second, meso analysis shows that Alan’s purpose in making the acronym are to entertain the audience and also to introduce Banyumas to the society widely. Third, maco analysis shows that the relationship between Alan and audience is equal.